Current and Emerging Diagnostic, Prognostic, and Predictive Biomarkers in Head and Neck Cancer - Hänel W. Eberly; Bao Y. Sciscent; F. Jeffrey Lorenz; Eleni M. Rettig; Neerav Goyal (Biomedicines, 2024)
Head and neck cancers (HNC) are a biologically diverse set of cancers that are responsible for over 660,000 new diagnoses each year. Current therapies for HNC require a comprehensive, multimodal approach encompassing resection, radiation therapy, and systemic therapy. With an increased understanding of the mechanisms behind HNC, there has been growing interest in more accurate prognostic indicators of disease, effective post-treatment surveillance, and individualized treatments. This chapter will highlight the commonly used and studied biomarkers in head and neck squamous cell carcinoma.